PENERAPAN MODEL PEMBELAJARAN PROJECT BASED LEARNING (PJBL) DALAM MATA PELAJARAN TEKNIK ANIMASI PADA SISWA KELAS XI DKV SMK NEGERI 3 PAREPARE - Amaliah Majid, Nur; S. Lamada, Mustari; Purnamawati (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
Abstract- The limited use of practical and project-based activities in the Animation Technique subject has hindered students’ skill development. In fact, animation learning requires active engagement through practice and project creation to achieve optimal learning outcomes and support future digital industry skills. In addition, low student achievement indicates that the learning process has not been optimal and lacks student involvement. This study employed Classroom Action Research (CAR) to improve students’ learning outcomes through the implementation of the Project Based Learning (PjBL) model in the Animation Technique subject for class XI DKV at SMK Negeri 3 Parepare. The subjects of this study were 27 students. Data were collected using observation sheets to assess student activity and test instruments to measure learning outcomes in each cycle. The results showed a consistent improvement in learning outcomes. The pre-test average score was 52.7 with a completion rate of 17.3%. In cycle I, the average score increased to 76.4 with a completion rate of 47.8%. In cycle II, a more significant improvement was achieved with an average score of 90.4 and a completion rate of 86.9%. These findings indicate that PjBL effectively improves learning outcomes and is recommended to enhance students’ activeness, creativity, and skills in animation projects.